2018
DOI: 10.1136/gutjnl-2018-317263
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative administration of the 5-HT4 receptor agonist prucalopride reduces intestinal inflammation and shortens postoperative ileus via cholinergic enteric neurons

Abstract: ObjectivesVagus nerve stimulation (VNS), most likely via enteric neurons, prevents postoperative ileus (POI) by reducing activation of alpha7 nicotinic receptor (α7nAChR) positive muscularis macrophages (mMφ) and dampening surgery-induced intestinal inflammation. Here, we evaluated if 5-HT4 receptor (5-HT4R) agonist prucalopride can mimic this effect in mice and human.DesignUsing Ca2+ imaging, the effect of electrical field stimulation (EFS) and prucalopride was evaluated in situ on mMφ activation evoked by AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 41 publications
1
104
0
1
Order By: Relevance
“…6a and f). In contrast, other receptors reported to be involved in cholinergic immune suppression such as receptors for serotonin 56 , catecholamine (ADRB2) 50, 57 , or neuropeptides (NMUR1, VIPR1, SSTR2, and CALCRL) 5865 were not upregulated in fiber-high LPMΦ compared to fiber-low LPMΦ or were not expressed (NMUR1) (Fig. 6b, c and f).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…6a and f). In contrast, other receptors reported to be involved in cholinergic immune suppression such as receptors for serotonin 56 , catecholamine (ADRB2) 50, 57 , or neuropeptides (NMUR1, VIPR1, SSTR2, and CALCRL) 5865 were not upregulated in fiber-high LPMΦ compared to fiber-low LPMΦ or were not expressed (NMUR1) (Fig. 6b, c and f).…”
Section: Resultsmentioning
confidence: 88%
“…Upon Salmonella typhimurium infection, MMΦ interact with sympathetic adrenergic neurons via β2 adrenergic receptors to induce a tissue- and neuron-protective gene expression program 50 . In a model of POI which is characterized by surgery-induced inflammatory response of MMΦ and impaired motility, VN stimulation or pharmacologic triggering of cholinergic enteric neurons prevented MΦ activation and reduced POI in a α7nAChR-dependent manner in both mice and humans 56 . However, anti-inflammatory neuro-immune modulation seems to involve different neuronal receptors in type 2-mediated intestinal disease models.…”
Section: Discussionmentioning
confidence: 97%
“…In animal studies, interventions have been explored aiming to reduce the early inflammatory responses that lie at the basis of POI. For instance, prucalopride, a5‐Ht4 receptor agonist, and vagus nerve stimulation, either electrical or via lipid‐enriched nutrition inhibits inflammation in an early stage and can prevent experimental POI 18,34,35 . Interestingly, two recent clinical pilot studies by Stakenborg et al showed promising results in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this discrepancy between the experimental data and the implementation into clinical practice may be twofold; on the one hand there is a lack of consensus amongst physicians toward the clinical features of POI, its impact, and its management, resulting in few high quality clinical studies also in a surgical setting 14 . On the other hand, it is uncertain whether the mechanisms found in rodent models can be completely translated into the clinical setting 15‐18 . The aim of the current study is to address whether inflammatory processes such as those found in experimental studies, occur in patients undergoing colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, mosapride ameliorates gastric hypomotility following vincristine‐induced colitis, whereas in human patients, mosapride increased gastric emptying and decreases full bowel transit time during capsule endoscopy . Preoperative administration of prucalopride shortens postoperative ileus and reduces intestinal inflammation in clinical patients with decreases in IL‐6 and IL‐8 expression . Utilizing the 5‐HT4 agonists in the treatment of acute inflammatory colitis is a promising option when prokinetic and neurogenic effects are desirable.…”
Section: Potential Neurogenic Pathwaysmentioning
confidence: 99%